The relation of European thought to the ‘logos’ and ‘logic’: a possible contribution to cultural world integration? - Beck, Heinrich (Scripta Neophilologica Posnaniensia, 2018)
The relation of European thought to the ‘logos’ and ‘logic’: a possible contribution to cultural world integration?